PKM GURU-GURU SDN 08 DAN SDN 16 CAMPAGO IPUH MANDIANGIN KOTO SELAYAN BUKITTINGGI DALAM PEMBELAJARAN KERAJINAN - Zubaidah Zubaidah Zubaidah; Erfahmi Erfahmi; maltha kharisma; Asra Ilal Khairi (Jurusan Seni Rupa, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2019)
The subjects of Cultural Arts and Skills / Crafts (SBdK / P) in Elementary Schools (SD) in accordance with the 2013 curriculum consist of fine arts, craft skills, music, dance, and drama. Learning SBDK / P in Elementary Schools is the most effective means for children's personal formation. Through this education rational, emotional, and motor activities will be met. The development of these three abilities is very important for the world of children's education, because SBDK / P education has a multilingual, multi-dimensional, and multicultural nature. Therefore teachers who teach arts and culture education and skills need to organize it well, so that learning objectives can be achieved optimally. The main problem in implementing SBDK / P learning, especially skills / craftsmanship is the lack of teacher's ability in the arts and crafts. This is generally felt by elementary school teachers, including SDN 08 and SDN 16, Mandiangin District, Koto Selayan Bukittinggi. Based on preliminary information that learning SBDK / P, especially fine arts and crafts has not been implemented well. The implementation of SBDK / P learning materials by teachers in SDN 08 and SDN 16 in particular was caused by the teachers not having a background in arts and crafts education. Besides that, opportunities for teachers to improve the ability of the arts and crafts outside of teaching tasks are relatively never found. Based on these problems an effort should be made to improve the ability of Elementary School teachers, especially in SDN 08 and SDN 16 Mandiangin Subdistrict, Koto Selayan Bukittinggi so that the implementation of SBDK / P learning, especially crafts / crafts, can be carried out properly the competencies expected by students can be achieved. In an effort to improve the ability of these teachers is to implement the Community Partnership Program (PKM) in particular providing training in woven crafts and montage artwork.